2007
DOI: 10.1111/j.1440-1746.2007.05108.x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and genetic factors associated with sacroiliitis in Crohn's disease

Abstract: We confirm the high prevalence of radiographic sacroiliitis in a multicenter CD cohort. Uveitis is only associated with AS whereas all patients with SI are more prone to develop peripheral arthritis during their disease course, suggesting similar pathogenetic mechanisms in the development of these EIM. The previously reported association between SI and CARD15 polymorphisms was not confirmed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
0
4

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(43 citation statements)
references
References 32 publications
2
37
0
4
Order By: Relevance
“…Pure asymptomatic SI in CD is not strongly associated with HLA-B27 and a very recent study indicates a prevalence of 7% (comparable to prevalence in the healthy population) [43] , and it seems that evolution to AS is more likely to occur in HLAB27-positive patients [59] . This suggests that SI and AS in IBD patients are different entities.…”
Section: Hla-b27mentioning
confidence: 99%
See 2 more Smart Citations
“…Pure asymptomatic SI in CD is not strongly associated with HLA-B27 and a very recent study indicates a prevalence of 7% (comparable to prevalence in the healthy population) [43] , and it seems that evolution to AS is more likely to occur in HLAB27-positive patients [59] . This suggests that SI and AS in IBD patients are different entities.…”
Section: Hla-b27mentioning
confidence: 99%
“…Souza et al [49] , in a mixed Brazilian IBD population found a prevalence of 14.4%, with no difference between CD and UC. Al-Shamali et al [50] reported [43] 2008…”
Section: Epidemiologymentioning
confidence: 99%
See 1 more Smart Citation
“…Seventy-eight percent of CD patients with sacroiliitis were carriers of at least one SNP in NOD2, compared to 48% of those who were wild type for NOD2. However, in a second multi-center study, this observation could not be repeated [102]. The reason for this inconsistency is not clear.…”
Section: Nod2 (16q)mentioning
confidence: 86%
“…Enthesitis or inflammation of insertion of tendon to bone occurs in about 7% of patients. The axial arthropathy includes inflammatory back pain present in 20-30% of patients, radiologic evidence of sacroiliitis in 20-25% of patients and full diagnosis of ankylosing spondylitis (AS) according to Rome criteria in 2-10% of patients [1][2][3] . Sacroiliitis and AS are diagnosed on conventional rheumatological grounds supported by characteristic radiologic changes, magnetic resonance imaging being the most sensitive.…”
Section: Clinical Evidencementioning
confidence: 99%